A diversity and functional approach to evaluate the macroinvertebrate responses to multiple stressors in a small subtropical austral river - J.H. Erasmus (Elsevier, 2021)
Aquatic macroinvertebrates are considered effective bioindicators of ecosystem health due to their different sensitivities to habitat alteration and pollution. Macroinvertebrate community structures can be assessed using commonly used diversity-based approaches, however, functional trait-based approaches are increasingly introduced into bioassessments. The Hex River is subjected to intensive mining activities, while urban and industrial effluents, as well as treated and untreated sewage also contributes to pollution in the river. The present study aimed to assess macroinvertebrate responses to different stressors (nutrient and chemical, especially metal pollutants), determine whether diversity-based or trait-based approaches provide a better indication of responses and, to evaluate the relationship between metal bioaccumulation and macroinvertebrate responses to this multi-stressor environment. The mining impacts, in combination with urban, industrial and sewage effluent, altered the macroinvertebrate community structure of the Hex River. The species richness significantly decreased from reference conditions (39 species) to impacted conditions (24 species), while the total number of individuals in tolerant species gradually increased. The diversity-based approach indicated a clear difference between reference and impacted conditions but did not clearly differentiate between different stressors, while the trait-based approach distinguished the urban, industrial and sewage effluent sites from mining impacted sites. The use of both approaches is, therefore, recommended as both complement each other. From the present study, it is evident that macroinvertebrates can be considered as both reliable accumulation-, and response bioindicators to pollution from mining, as well as urban and industrial activities.